Peripheral T-cell lymphomas: analysis of histology, staging and response to treatment of 208 cases at a single institution. Issue 11 (November 2013) - Broussais-Guillaumot, Florence; Coso, Diane; Belmecheri, Nawel; Ivanov, Vadim; Schiano de Collela, Jean-Marc; Aurran-Schleinitz, Thérèse; Stoppa, Anne-Marie; Chetaille, Bruno; Xerri, Luc; Esterni, Benjamin; Blaise, Didier; Bouabdallah, Reda
Abstract Peripheral T-cell lymphomas are characterized by a poor clinical outcome. We retrospectively analyzed 208 adults treated in our institution between 2000 and 2011. Median age at diagnosis was 55 years. Fifty-one percent had B symptoms and 51% serum elevated lactate dehydrogenase (LDH) levels. Eastern Cooperative Oncology Group (ECOG) performance status (PS) was 0–1 in 63% and 2–4 in 37%. According to Ann Arbor classification, 16% were at stage I–II and 84% at stage III–IV. Histological subtypes were: 39% peripheral T-cell non-Hodgkin lymphoma (NHL) unspecified (PTCL-U), 19.5% anaplastic large cell lymphoma (ALCL), with 9.5% ALK+ and 10% ALK−, and 25% angioimmunoblastic lymphoma (AILT). Primary extranodal lymphoma represented 17%, and 8% were diagnosed with hemophagocytosis. Induction chemotherapy was CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) in 87% of patients. The median number of chemotherapy cycles was 2 (1–7). A complete response was obtained in 57% of the patients. Among them, 32% had an autologous stem cell transplant (ASCT) and 10% allogeneic SCT, while 38% were primary refractory. Five-year overall survival (OS) was 28.5% (22.3–36.3), and 5-year event-free survival (EFS) was 18.4% (13.4–25.3). A multivariate analysis showed that ALCL-ALK+ (p = 0.004), AILT (p < 0.01), extranodal involvement (p = 0.001), PS > 1 (p = 0.04), LDH < normal (p = 0.003) and hemophagocytosis (p = 0.001) were independent adverse factors for OS. We conclude that conventional chemotherapy with intensive treatment is not sufficient to improve the response rate. Optimal management is required.